Cannabinoid CB1 receptor neutral antagonist AM4113 inhibits heroin self-administration without depressive side effects in rats - He Xiang-hu; Jordan Chloe J.; Vemuri Kiran; Bi Guo-hua; Zhan Jia; Gardner Eliot L.; Makriyannis Alexandros; Wang Yan-lin; Xi Zheng-xiong (Acta Pharmacologica Sinica, 2019)
Cannabinoid CB1 receptors (CB1Rs) have been shown to be a promising target in medication development for the treatment of addiction. However, clinical trials with SR141716A (rimonabant, a selective CB1R antagonist/inverse agonist) for the treatment of obesity and smoking cessation failed due to unwanted side effects, such as depression, anxiety, and suicidal tendencies. Recent preclinical studies suggest that the neutral CB1R antagonist AM4113 may retain the therapeutic anti-addictive effects of SR141716A in nicotine self-administration models and possibly has fewer unwanted side effects. However, little is known about whether AM4113 is also effective for other drugs of abuse, such as opioids and psychostimulants, and whether it produces depressive side effects similar to SR141716A in experimental animals. In this study, we demonstrated that systemic administration of AM4113 (3 and 10 mg/kg) dose-dependently inhibited the self-administration of intravenous heroin but not cocaine or methamphetamine, whereas SR141716A (3 and 10 mg/kg) dose-dependently inhibited the self-administration of heroin and methamphetamine but not cocaine. In the electrical brain-stimulation reward (BSR) paradigm, SR141716A (3 and 10 mg/kg) dose-dependently increased the BSR stimulation threshold (i.e., decreased the stimulation reward), but AM4113 had no effect on BSR at the same doses, suggesting that SR141716A may produce aversive effects while AM4113 may not. Together, these findings show that neutral CB1R antagonists such as AM4113 deserve further research as a new class of CB1R-based medications for the treatment of opioid addiction without SR141716A-like aversive effects.